Clinical outcomes of and management strategy for perforations associated with endoscopic submucosal dissection of an upper gastrointestinal epithelial neoplasm - Kim, Hyun Ju; Chung, Hyunsoo; Jung, Da Hyun; Park, Jun Chul; Shin, Sung Kwan; Lee, Sang Kil; Lee, Yong Chan (Surgical endoscopy, 2016)
Introduction Perforation is one of the major complications of endoscopic submucosal dissection (ESD). In the present study, we investigated the clinical outcomes of and management strategies for ESD-related perforations. Methods Between February 2010 and April 2014, a total of 3821 patients who underwent ESD for an upper gastrointestinal epithelial neoplasm were analyzed using the Yonsei University Severance Hospital database. Clinical outcomes of and management strategies for perforations in 90 patients (2.4 %) were analyzed. The risk factors for the development of perforation were also investigated. Results The mean age of our subjects was 64.7 ± 12.2 years (male to female ratio, 3.2:1), and the mean size of the resected specimens was 39.4 ± 12.5 mm. Endoscopically visible perforations (visible perforation group) were noted in 74 of the 90 patients (82.2 %), and clinically suspected perforations (suspected perforation group) were noted in 16 patients (17.8 %). Immediate closure with endoclips was attempted in cases with a visible perforation and was successful in 72 (97.3 %) cases. Two patients in whom endoscopic closure failed underwent surgery. Conservative care, including fasting and intravenous antibiotic administration, was attempted in the suspected perforation group, and all the patients were treated successfully without surgery. The mean durations of fasting, antibiotic treatment, and hospital stay were 3.8 ± 3.1, 6.8 ± 4.2, and 8.7 ± 5.3 days, respectively. Subgroup analysis of perforation type (visible perforation vs. suspected perforation) revealed no significant difference in the clinical course. Tumor location at the upper or middle third of the stomach was significantly associated with perforation. Conclusion Most of the ESD-related perforations in upper gastrointestinal epithelial neoplasm could be managed successfully in a non-surgical manner under strict monitoring.